The 1st International Electronic Conference on Pharmaceutics 2020
DOI: 10.3390/iecp2020-08671
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls of Accurate Protein Determination inside PLGA Nanoparticles Using the Micro BCA Assay

Abstract: Cancer is one of the leading causes of death in the world and protein therapeutics play an important role in combating this disease. Novel nanocarriers are needed for optimal delivery, enhanced therapeutic effect, and protection of proteins. Poly Lactic-co-Glycolic Acid (PLGA) nanoparticles are commonly used, since they are non-toxic, biodegradable, and allow for the sustained release of the active pharmaceutical ingredient (API). Accurate quantification of the therapeutic inside these nanocarriers is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Although the Kjeldahl technique is regarded as the worldwide standard and therefore simple to compare findings with other laboratories, it does not measure real protein and can result in overestimation of protein owing to the use of the standard nitrogen correction factor 14 . On the other hand, the BCA technique, which is used in the present study, is based on two chemical reactions, including the biuret reaction, which reduces cupric ions (Cu 2+ ) to cuprous ions (Cu 1+ ) via peptide bonds and the chelation of one Cu 1+ molecule with two BCA molecules to form a bright purple complex which is spectrophotometrically detected 15 . Besides, BCA is simpler, ease of use, takes less time for the experiment, requires fewer instruments, high sensitivity, and tolerance of interfering species, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Kjeldahl technique is regarded as the worldwide standard and therefore simple to compare findings with other laboratories, it does not measure real protein and can result in overestimation of protein owing to the use of the standard nitrogen correction factor 14 . On the other hand, the BCA technique, which is used in the present study, is based on two chemical reactions, including the biuret reaction, which reduces cupric ions (Cu 2+ ) to cuprous ions (Cu 1+ ) via peptide bonds and the chelation of one Cu 1+ molecule with two BCA molecules to form a bright purple complex which is spectrophotometrically detected 15 . Besides, BCA is simpler, ease of use, takes less time for the experiment, requires fewer instruments, high sensitivity, and tolerance of interfering species, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, BCA is simpler, ease of use, takes less time for the experiment, requires fewer instruments, high sensitivity, and tolerance of interfering species, e.g. common surfactants 15 17 . The findings revealed that the protein contents analyzed by BCA in the current investigation were equivalent to those found in the prior study utilizing the Kjeldahl method.…”
Section: Resultsmentioning
confidence: 99%
“…[131,132] However, absorption by functional groups in the polymer/crosslinkers or scattering interferences due to NG concentration may lead to inaccurate results. [133][134][135][136] A frequently used strategy is based on labeled proteins that can be quantified by colorimetric or fluorometric methods. For example, Duan et al studied the loading of different FITC-labeled proteins into dual-responsive NGs to develop multifunctional carriers for combined cancer therapy.…”
Section: Direct Determinationmentioning
confidence: 99%
“…[ 131,132 ] However, absorption by functional groups in the polymer/crosslinkers or scattering interferences due to NG concentration may lead to inaccurate results. [ 133–136 ] A frequently used strategy is based on labeled proteins that can be quantified by colorimetric or fluorometric methods. For example, Duan et al.…”
Section: Protein Encapsulation and Releasementioning
confidence: 99%
“…Apolinário et al, 2019 descrevem que há uma superestimação da quantificação de proteínas quando a metodologia indireta é realizada, possivelmente, pela interação da cadeia polimérica, é possível aprisionamento de moléculas de enzima livre, que acabam sendo consideradas no cálculo da concentração de enzima encapsulada. Essa questão é abordada por outros autores, os quais levantam o questionamento sobre a possibilidade de falhas na estimativa da EE%, especialmente pela metodologia indireta (APOLINÁRIO et al, 2019;CLERICI et al, 2021).…”
Section: Nanoencapsulação Da Catalase Em Polimerossomasunclassified